The imitation game – exploring the double-grip analysis for creating analog wines - Crichton-Fock, APF; Spence, C (Taylor and Francis, 2024)
In this pilot study, we investigated the use of the Double-Grip Analysis method as a tool to create analogue wines. The study involved four groups of sommeliers using the method to identify critical analytical and analogical attributes in four commercial wines. The basis of communication with this method is via the use of analogies, metaphors, and practical examples that emerge during the analysis and the dialogue. An overmatured rosé wine with mature flavours and low acidity served as the base for all groups when replicating the commercial counterparts making analogue wines. At first, the study aimed to assess the sommeliers’ ability to use this method in blending and wine production. In addition, the study explored the acceptability of these analogue wines, as they aim to replicate sensory characteristics of commercial counterparts, providing environmentally friendly alternatives. A panel of 20 consumers evaluated the quality of the wines as guests at a blind tasting dinner. The results help to shed light on the effectiveness of the Double-Grip Analysis Method, while at the same time providing insights into the acceptability of these analogue products amongst consumers. This research contributes to the field of culinary exploration and sustainable alternatives in the wine industry.